Alterations of the Gut Microbiome and Metabolome in Patients With Proliferative Diabetic Retinopathy - Ye, Panpan; Zhang, Xueyou; Xu, Yufeng; Xu, Jia; Song, Xiaoxiao; Yao, Ke (Frontiers in Microbiology, 2021)
Diabetic retinopathy (DR) has been reported to associate with gut microbiota alterations in murine models and thus “gut-retina-axis” has been proposed. However, the role of gut microbiome and the associated metabolism in DR patients still need to be elucidated. In this study, we collected fecal samples from 45 patients with proliferative DR (PDR) and 90 matched diabetic patients (1:2according to age,sex and duration of diabetes) without DR (NDR) and performed 16S rRNA gene sequencing and untargeted metabolomics. We observed significantly lower bacterial diversity in PDR group than that in NDR group. Differential gut bacterial composition was also found, with significant depletion of 22 families (e.g., Coriobacteriaceae, Veillonellaceae and Streptococcaceae) and enrichment of 2 families (Burkholderiaceae and Burkholderiales_unclassified) in PDR group ascompared to NDR group. There weresignificantly different fecal metabolic features, which wereenriched in metabolic pathways such as arachidonic acid and microbial metabolism, between the two groups.Among 36 co-abundance metabolite clusters, 11 were positively/negatively contributed to PDR using logistic regression analysis. Fifteen gut microbial families were significantly correlatedwith the 11 metabolite clusters. Furthermore, a fecal metabolites-based classifier was constructed to distinguish PDR patients from NDR patients accurately. In conclusion, PDR is associated with reduced diversity and altered composition of gut microbiota andspecific microbe-metabolite interplay.Our findings help to better understand the disease pathogenesis and provide novel diagnostic biomarkers and therapeutic targets for PDR.